2023
DOI: 10.1002/pen.26343
|View full text |Cite
|
Sign up to set email alerts
|

Impact of thermomechanical reprocessing conditions on polypropylene composites made from automotive waste parts: A path to a circular economy

Abstract: This work focused studying waste car bumper samples and their processing by re-extrusion-injection. Car bumpers are composed of crystalline phases of polypropylene (PP), talc, and amorphous ethylene propylene diene monomer (EPDM). The recycled material's thermal, mechanical, and structural properties depend strongly on the process used for extrusion and injection and the crystalline phases formed during the heating process. The FWHM of the x-ray diffraction patterns was used to study the recrystallization phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The recipe being a trade secret has been an obstacle, as the exact composition of TPO/PP is unknown to many. The knowledge of physicochemical properties is a major factor in addition to the operating conditions of the recycling process [26]. While the European commission regulation on end-of-life vehicles (ELVs) have established goals for a recyclable system, the United States Department of Energy proposed a plan for a 95% recycling rate target for automobiles, which includes metals, plastics, and other materials.…”
Section: Sustainability Aspectmentioning
confidence: 99%
See 1 more Smart Citation
“…The recipe being a trade secret has been an obstacle, as the exact composition of TPO/PP is unknown to many. The knowledge of physicochemical properties is a major factor in addition to the operating conditions of the recycling process [26]. While the European commission regulation on end-of-life vehicles (ELVs) have established goals for a recyclable system, the United States Department of Energy proposed a plan for a 95% recycling rate target for automobiles, which includes metals, plastics, and other materials.…”
Section: Sustainability Aspectmentioning
confidence: 99%
“…To that extent, researchers have worked with environment aging and oxidation processes [49][50][51]. Recently, bumpers from automotive waste were recycled via re-extrusion-injection and it was observed that the removal of micro paint particles is a critical factor for improving the mechanical properties, in addition to non-damp storage conditions [26]. In another case study by Guo et al, the paint removal process was carried out via plastic shot peening followed by the addition of nano-montmorillonite, virgin PP, recycled PP, and a compatibilizer.…”
Section: Sustainability Aspectmentioning
confidence: 99%
“…Just in 2019, it was reported that the global plastic market had stretched to 368 million tons, and it is projected to rise to 417 million tons by 2030 and double by 2050. [1][2][3][4][5][6][7] The linear global plastics economy, with its "take, make, use, and waste" approach, is responsible for the majority of plastic products being discarded without repurposing after reaching the end of their life. Also, it is worth mentioning the production leftovers, which take up a notable amount of total plastic waste.…”
Section: Introductionmentioning
confidence: 99%